Morphological Map Analysis in Design Cashew Sheller (Kacip) As a Creative Proccess to Produce Design Concept - Wahyujati, Bertha Bintari (International Journal of Applied Sciences and Smart Technologies, 2019)
The design of cashew nut or cashew nut sheller uses appropriate or low technology with consideration of low cost for tool material. This pengkacip tool will be used at Ngudi Koyo, Imogiri, Bantul, Yogyakarta. Cashew shell peeler or cippling device as a result of the design is a modification of the existing cashew shell peeler. Some parts of the existing tool are applied to several modified parts, namely the lever mechanism, picking knife, or lever knife. This paper will discuss the method of selecting a suppressor, lever and picking system on a tool using the morphological map analysis method. Morphological maps will produce alternative designs for cashew nut peeler. The selection of alternative designs will be carried out by analyzing the results of testing in a technical mechanism, material strength, and alternative design quality values. Testing of alternative technical systems mechanisms is done by comparing the mechanical systems of existing tools. The size of the tool uses the anthropometric measurements of the female operator's body, because the operators in the Ngudi Koyo UKM are all women. The tool size adjustment will provide work comfort and increase efficiency. Quality testing in addition to using standard anthropometric standards, will be tested for quality of ease of care, ease of transferring, clean, neat, simple and safe  tool.Key words: Effective technology , low technology tool, security, Design Alternative Testing